1997
DOI: 10.1093/arclin/12.3.231
|View full text |Cite
|
Sign up to set email alerts
|

The effect of warning on malingering on memory and motor tasks in college samples

Abstract: The effect of a warning regarding detection of simulated cognitive and motor deficits on the Wechsler Memory Scale-Revised (WMS-R; Wechsler, 1987) and Grooved Pegboard (Klove, 1963; Matthews & Klove, 1964) was examined. Undergraduates (N = 87) were randomly assigned to one of three conditions: simulators without warning, simulators with warning, and controls. It was predicted that warning participants that simulation efforts will be detected would reduce malingering behavior and this hypothesis was generally s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 12 publications
1
8
0
2
Order By: Relevance
“…All malingering indexes, and 17 of the 18 psychopathology scales where malingering was successfully induced, showed an impact of warning, with one scale demonstrating partial support for a warning effect. This finding is consistent with studies supporting the utility of warning to reduce malingering on neuropsychological measures (Erdal, 2004;Gunstad & Suhr, 2001;Johnson & Lesniak-Karpiak, 1997;Suhr & Gunstad, 2000) and faking good on personality inventories (Braun & Faro, 1968;Nias, 1972). The use of a theoretically informed warning method and a bona fide sanction in this study may help explain why previous research has sometimes failed to find a warning effect (Johnson et al, 1998;Slick et al, 1994;Suhr et al, 2004;Sullivan et al, 2001;Wong et al, 1998).…”
Section: The Utility Of Warning To Deter Malingeringsupporting
confidence: 91%
See 1 more Smart Citation
“…All malingering indexes, and 17 of the 18 psychopathology scales where malingering was successfully induced, showed an impact of warning, with one scale demonstrating partial support for a warning effect. This finding is consistent with studies supporting the utility of warning to reduce malingering on neuropsychological measures (Erdal, 2004;Gunstad & Suhr, 2001;Johnson & Lesniak-Karpiak, 1997;Suhr & Gunstad, 2000) and faking good on personality inventories (Braun & Faro, 1968;Nias, 1972). The use of a theoretically informed warning method and a bona fide sanction in this study may help explain why previous research has sometimes failed to find a warning effect (Johnson et al, 1998;Slick et al, 1994;Suhr et al, 2004;Sullivan et al, 2001;Wong et al, 1998).…”
Section: The Utility Of Warning To Deter Malingeringsupporting
confidence: 91%
“…The finding that the effects of warning extended to most scales on both measures and to all malingering indexes differs somewhat from past neuropsychological warning research that has found warning to have a more selective and differential effect across measures. For instance, Johnson and Lesniak-Karpiak (1997) found warning effective on three of five WMS-R memory indexes, whilst Erdal (2004) found that warning reduced malingering on the DCT but not on the Rey FIT, even though these tests measure similar constructs. The relatively robust and less differentiated warning effect found in the present study suggests that the warning method may account for much of the variation in warning effects found in previous studies.…”
Section: The Utility Of Warning To Deter Malingeringmentioning
confidence: 99%
“…The Johnson et al (1997) results have not been replicated. Johnson was unable to replicate her initial findings; instead she found that warned and unwarned simulators performed similarly (Johnson, Bellah, Dodge, Kelley, & Livingston, 1998).…”
mentioning
confidence: 88%
“…Rogers and Cavanaugh (1983) illustrate the absurdity of asking undergraduates to comply with instructions to fake deficits, in order to draw conclusions about real-life litigants who fake deficits in defiance of compliance expectations. Empirically, the ''forewarning improves motivation'' belief is linked to a single study, a role-play simulation by Johnson and Lesniak-Karpiak (1997). Johnson et al asked undergraduates to feign neuropsychological deficits for imaginary compensation, and found an effect for warning: A warned group produced higher motor and memory scores than unwarned (''naı¨ve'') simulators.…”
Section: Forewarning Guarantees Motivationmentioning
confidence: 99%
“…Some studies have examined whether warnings against malingering would reduce the likelihood of malingering in nonclinical volunteers (Erdal, 2004;Johnson & Lesniak-Karpiak, 1997;Suhr & Gunstad, 2000;Sullivan & Richer, 2002). For example, Erdal found that warning student simulators about malingering detection measures reduced the degree of symptom exaggeration on memory tasks but not on timed tasks.…”
mentioning
confidence: 99%